THE JADID MOVEMENT AND ITS INFLUENCE ON THE DEVELOPMENT OF UZBEK SOCIETY - M. Misrbekova (Western European Studies, 2025)
This article analyzes the influence of the Jadid movement, which emerged in the late 19th and early 20th centuries, on the development of Uzbek society from a scholarly perspective. The educational ideas, reformist activities, and contributions of the Jadids in the fields of press, literature, and education are examined based on historical sources. The article highlights the movement's role in awakening social consciousness, shaping modern thinking, and forming a civil society
Keywords: Jadidism; reform; enlightenment